Extending T-Res with mobility for context-aware IoT - Gaur, Shashank (2016)
1st IEEE International Conference on Internet-of-Things Design and Implementation (IoTDI 2016). 4 to 8, Apr, 2016, I4T Workshop. Berlin, Germany.